Peer review of the pesticide risk assessment of the active substance clove oil - European Food Safety Authority (EFSA); Fernando Álvarez; Maria Arena; Domenica Auteri; Sofia Batista Leite; Marco Binaglia; Anna Federica Castoldi; Arianna Chiusolo; Angelo Colagiorgi; Mathilde Colas; Federica Crivellente; Chloe De Lentdecker; et al. (EFSA Journal)
Abstract The conclusions of the EFSA following the peer review of the initial risk assessments carried out by the competent authority of the rapporteur Member State, Malta, for the pesticide active substance clove oil are reported. The context of the peer review was that required by Regulation (EC) No 1107/2009 of the European Parliament and of the Council. The conclusions for the amendment of approval were reached on the basis of the evaluation of the representative use of clove oil as a preharvest nematicide on tomatoes and cucumbers (permanent greenhouse use). The representative use evaluated for the renewal of approval of clove oil was as post‐harvest fungicide and bactericide on apples, pears and peaches (indoor uses). The reliable endpoints appropriate for use in regulatory risk assessment are presented. Endpoints not relevant to the scope of the proposed amendment of approval conditions will be addressed in the context of the renewal of approval procedure of clove oil running in parallel (AIR IV, EFSA Q‐2016‐00809). Missing information identified as being required by the regulatory framework is listed. Concerns are reported where identified.